Anticoagulant and antithrombotic effects of chemically sulfated fucogalactan and citrus pectin. (15th October 2017) - Román, Yony; de Oliveira Barddal, Helyn P.; Iacomini, Marcello; Sassaki, Guilherme L.; Cipriani, Thales R.
Highlights: Agaricus bisporus fucogalactan and β-glucan, and citrus pectin were isolated. The polysaccharides were chemically sulfated under optimized conditions. Anticoagulant activity of the sulfated polysaccharides was evaluated. Antithrombotic effect of the sulfated fucogalactan and citrus pectin was showed. Abstract: Citrus pectin (CP14) from Citrus sinensis, and a fucogalactan (E) and a glucan (G16) from Agaricus bisporus were isolated and structurally characterized. CP14 was constituted by (1→4)-linked α-d -Gal p A units, E was composed by a (1→6)-linked α-d -Gal p main-chain, partially substituted at O-2 by non-reducing end-units of α-l -Fuc p or α-d -Gal p, and partially methylated at O-3, whereas G16 was composed of (1→6)-linked β-d -Glc p units. The polysaccharides were sulfated giving rise to CP14S, ESL and G16S. The APTT and PT assays showed a decreasing order of anticoagulant activity for ESL, CP14S and G16S, respectively. ESL and CP14S showed greater anticoagulant activity. However, ESL reduced thrombus formation to 32.3% at a dose of 6.0 mg kg −1, whereas CP14S inhibited totally the thrombus formation at 3.0 mg kg −1, in vivo . NMR and methylation analyses showed that α-d -GalA p units of CP14S were sulfated in 2, 3- O -position, whereas ESL was mainly sulfated in 2- O -, 2, 3- O - and 2, 3, 4- O -positions.